2012
DOI: 10.3748/wjg.v18.i38.5476
|View full text |Cite
|
Sign up to set email alerts
|

Metachronous penile metastasis from rectal cancer after total pelvic exenteration

Abstract: Despite its abundant vascularization and extensive circulatory communication with neighboring organs, metastases to the penis are a rare event. A 57-year-old male, who had undergone total pelvic exenteration for rectal cancer sixteen months earlier, demonstrated an abnormal uptake within his penis by positron emission tomography/computed tomography. A single elastic nodule of the middle penis shaft was noted deep within Bucks fascia. No other obvious recurrent site was noted except the penile lesion. Total pen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 9 publications
0
37
0
Order By: Relevance
“…The most common symptoms noted, were palpable nodule, lesion/ulceration, priapism and difculty voiding. Two patients had no symptoms [7,8]. In our case, the patient complained of difcult voiding, pain and swelling in the scrotum and penis.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…The most common symptoms noted, were palpable nodule, lesion/ulceration, priapism and difculty voiding. Two patients had no symptoms [7,8]. In our case, the patient complained of difcult voiding, pain and swelling in the scrotum and penis.…”
Section: Discussionmentioning
confidence: 59%
“…The favoured non-invasive imaging modality to delineate the extent of involvement of the penis is MRI [5,7]. On T1-weighted images, lesions have low signal intensity, isointense with the surrounding corpus cavernosum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,8 Nevertheless, some authors have reported long survival cases. In 1961, Abeshouse 9 documented two patients surviving over nine years after their cancer diagnosis -in one case, the metastasis to the glans penis was treated with low dose rate brachytherapy and, in the other one, with surgical excision and adjuvant external radiotherapy.…”
mentioning
confidence: 99%